Cellular Mobile Base Station Radiation at Baghdad - Adheed Hasan Sallomi (Journal of Madenat Alelem University College, 2012)
Growing demand for mobile communication services results in a continuous increase in the number of base stations over a limited area, accompanied by public concern about the possible health and ecological effect of these systems. The main contribution of this paper is the usage of an empirical radio wave propagation model based on practical measurements in some ASIACELL sites in the city of Baghdad to measure the received signal power at the ground level in the vicinity of base stations and to determine the power- distance gradient value. The extracted power gradient value was used to examine the electromagnetic energy levels due to the base station transmitters. The calculated values of the power density levels in the vicinity of base stations were compared with the widely employed safety guidelines to ensure compliance with these standards. It was found that the exposure levels produced by the base station are too low compared with the exposure standards.